1992
DOI: 10.1902/jop.1992.63.8.701
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Effects of the Nd:YAG Laser on Root Surfaces and Subgingival Microflora In Vivo

Abstract: The purpose of this study was to examine the effects of root preparation using the pulsed Nd:YAG laser, either alone or in combination with manual instrumentation. Study specimens consisting of 18 teeth with associated periodontal pockets from 8 different patients were treated as follows: 5 specimens were root planed with curets followed by laser exposure for 3 minutes using energy settings of 3.0 W at 20 pps; 2 specimens were root planed and then laser treated for 3 minutes using settings of 2.25 W and 20 pps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 18 publications
4
126
0
7
Order By: Relevance
“…These observations provide cause for concern regarding potential thermal, pulpal damage in the clinical situation. 3) In case of open and closed PDL insertion sites in the cementum after Nd: YAG laser irradiation, a comparison between the fluorosed and non-fluorosed groups showed similar findings (p>0.05). Depending on the choice of laser parameter the effect on PDL insertion sites into cementum varied from total obliteration of insertion sites to little or no effect, the latter resulting in exposed and distinctly open sites.…”
Section: Discussionmentioning
confidence: 63%
“…These observations provide cause for concern regarding potential thermal, pulpal damage in the clinical situation. 3) In case of open and closed PDL insertion sites in the cementum after Nd: YAG laser irradiation, a comparison between the fluorosed and non-fluorosed groups showed similar findings (p>0.05). Depending on the choice of laser parameter the effect on PDL insertion sites into cementum varied from total obliteration of insertion sites to little or no effect, the latter resulting in exposed and distinctly open sites.…”
Section: Discussionmentioning
confidence: 63%
“…In a similar in vivo study, Cobb et al (26) observed ineffective and patchy removal of deposits on the root surface, associated with areas of cratering and meltdown. A post-treatment decrease in microbial levels was also reported.…”
mentioning
confidence: 80%
“…component of the radiation and, sometimes, local transient heating. The delivery of light to packaging materials, food surfaces and to transparent liquid products, in short pulses of high intensity has been shown to be capable of inactivating vegetative and spore forms of micro-organisms in these environments (Dunn et al 1988) and in the medical area, particularly dentistry (Powell & Wisenart, 1991;Cobb et al 1992;Rooney et al 1994).…”
Section: Other New and Emerging Physical Technologiesmentioning
confidence: 99%